Studies on genetic diversity in sesame (Sesamum indicum L.) over seasons: Studies on genetic diversity in sesame (Sesamum indicum L.) over seasons - PRAVEENKUMAR S; S T PONSIVA; A P T RAJKAPUR HARTIABINESARAJA; S SELVAMANI; S RANJITH RAJARAM; S THIRUGNANAKUMAR (Journal of Oilseeds Research, 2020)
D2 analysis of the sixty genotypes based on sixteen characters confirmed the presence of high diversity. Genotypes of different eco-geographic origins were grouped in a single cluster as well as in different clusters. Out of these twelve genotypes only five genotypes viz., G27, G32, G35, G39 and G40 showed high mean seed yield.